Marka hakkının sona ermesi - Eser, Habibe (My University, 2005)
MARKA HAKKININ SONA ERMESİ Ekonominin hızla gelişmesi, uluslararası ticaretin artması markanın korunmasını zorunlu hale getirmektedir. Gümrük birliğine katıldığımız, AB'ye başvurduğumuz bir dönemde marka hukuku büyük önem arz etmektedir. Markayı oluşturmak büyük emek, zaman ve maddi imkan gerektirmektedir. Büyük gayretlerle oluşturulan marka, çoğu zaman temsil ettiği mal/ hizmetin önüne geçmekte ve tek başına müstakilen ekonomik değere sahip olmaktadır. Marka hukukunun önemi ve yeni bir alan olması sebebi ile tez konusunu marka hukukundan seçtim ve tezimin konusu marka haklarının sona ermesidir. 556 sayılı Kanun Hükmünde Kararname kapsamında, Doktrin ve Yargıtay kararları ışığı altında değerlendirilmeye çalışılacaktır. Marka hakkının sona ermesinden bahsedebilmek için öncelikle marka hakkının kazanılması kavramının bilinmesi gerektiğinden öncelikle marka hakkının kazanılması açıklanmaya çalışılmıştır. Markalar Kanun Tasarısının getirdiği düzenlemeler de konu ile ilgili bölümlerde açıklanmıştır. Kanunsuz suç ve ceza olmaz ilkesi gereğince konunun kanunla düzenlenmesi daha doğru olacağından Markalar Kanun Tasarısı ile getirilen düzenlemenin daha isabetli olduğu kanaatindeyim. Marka hakkının sona ermesi doktrin ve Yargıtay kararları ışığı altında incelenerek sonuçlar ortaya konulmuş ve çözümler belirtilmiştir.

TERMİNATİON OF THE RİGHT OF TRADEMARK Rapid development of the economy, increase in the volume of the international commerce brings the issue of protection of trademarks before us as an obligatory matter. Law of trademarks has gained much more importance in today's period of customs union and recourse for full membership to EU. It requires great effort, time and material resources to establish a trademark. Trademarks which outcome from these great efforts generally pass ahead the product/ services they represent and turn into economic values themselves. I've chosen subject of my project from among the law of trademark topics because of the importance and innovative nature of this field. Namely subject of my project is termination of the right of trademark. The subject shall be evaluated in context of the Statutory Decree No. 556 and the legal precedents depends upon Court of Cassation Decisions. Since the right of trademark needs to be acquired in order to be terminated, project also involves explanation regarding the topic acquisition of right of trademarks. Regulations envisaged by the Draft Law of Trademarks are also explained under the related sections. To me, regulations of Draft Law of Trademarks seem to be more appropriate as the principle of there is neither crime nor punishment without law is taken into the consideration. Finally termination of the right of trademark is studied in the light of doctrine and legal precedents; conclusions are laid down and solutions are put forth.
Keywords: Hukuk; Marka Hukuku; Özel hukuk; Ticaret hukuku